أثر إنجاز تعلم اللغة العربية علي قدرة حفظ القرآن بمدرسة المتوسطة نور الإسلام تنجاران: أثر إنجاز تعلم اللغة العربية علي قدرة حفظ القرآن بمدرسة المتوسطة نور الإسلام تنجاران - Ainy Faizah (LP2M IAIN Sultan Amai Gorontalo, 2020)
Abstract This research is one of the attempts to find out the role of the achievement of learning the Arabic language on the ability to memorize the Qur’an among the students at junior high school of Nurul Islam Tengaran. The main issues that the researcher will answer in this research are (1) How was the achievement of learning Arabic language among the students at junior high school of Nurul Islam Tengaran? (2) How was the ability to memorize the Qur’an among the students at junior high school of Nurul Islam Tengaran? (3) Is there an impact of the achievement of learning the Arabic language on the ability to memorize the Qur’an among the students at junior high school of Nurul Islam Tengaran?.To answer these questions, the researcher uses a quantitative approach. The method used by the researcher to collect data is the method of questionnaire, viewing, and documentation. To analyze the data, the statistical methods are used by Product Moment symbols and the percentage according to the subject of the research means the correlation. The results of this research are: The achievement of learning the Arabic language in the students at junior high school of Nurul Islam Tengaran, be on a high bike because most of them get a high score or greater than the minimum completion of the calibrated. As for the hypothesis test, there is the effect of the achievement of learning the Arabic language on the ability to memorize the Qur'an among the students at junior high school of Nurul Islam Tengaran. Given that the research, which was analyzed by statistical method with the symbols of Product Moment, obtained the result (rxy) = 0,891 and agreed with the table of Product Moment N = 34, in the order of significance 5% is 0,339 and the significance levels of 1% are 0,436. This includes the result of (rxy) more than table (r) or in other words (0,891> 0,436 >0,339). Keywords : The achievement of learning, Arabic language, The ability to memorize the Qur’an